2014
DOI: 10.1002/clc.22304
|View full text |Cite
|
Sign up to set email alerts
|

Modern Obesity Pharmacotherapy: Weighing Cardiovascular Risk and Benefit

Abstract: Obesity is a major correlate of cardiovascular disease. Weight loss improves cardiovascular risk factors and has the potential to improve outcomes. Two drugs, phentermine plus topiramate and lorcaserin, have recently been approved by the US Food and Drug Administration for the indication of obesity; a third, bupropion plus naltrexone, is under consideration for approval. In clinical trials, these drugs cause weight loss and improve glucose tolerance, lipid profile, and, with the exception of bupropion plus nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
0
20
0
2
Order By: Relevance
“…Research has shown that pharmacotherapy results can range from very substantial weight loss to modest or no weight loss [72]. The FDA and medical community have been slow to adopt the use of current weight loss medications secondary to a history of harmful medications and their use in the past, such as Fen-Phen, a previously approved combination of fenfluramine and phentermine, which was widely prescribed and caused pulmonary hypertension and heart valvulopathy [73]. Nevertheless, the obesity epidemic necessitates the ongoing consideration of the medical community to consider the proper use of pharmacotherapy in the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that pharmacotherapy results can range from very substantial weight loss to modest or no weight loss [72]. The FDA and medical community have been slow to adopt the use of current weight loss medications secondary to a history of harmful medications and their use in the past, such as Fen-Phen, a previously approved combination of fenfluramine and phentermine, which was widely prescribed and caused pulmonary hypertension and heart valvulopathy [73]. Nevertheless, the obesity epidemic necessitates the ongoing consideration of the medical community to consider the proper use of pharmacotherapy in the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Most, if not all, of the pharmacologic agents that reduce body weight are designed to induce satiety (7). Some of the common adverse effects associated with the available antiobesity drugs are hypertension and valve disease (8). Although antiobesity drugs elicit approximately 5% weight reduction, people will not be able to maintain the weight reduction for prolonged periods, highlighting the need for efficacious and safe alternatives (9).…”
mentioning
confidence: 99%
“…Ле-чение ожирения и его осложнений занимает одну из гла-венствующих позиций в современной науке, при этом эффективных методов все еще недостаточно [4,5,50]. Изучение микрофлоры кишечника с позиции влияния на ожирение и развития метаболического синдрома только начинается.…”
Section: заключениеunclassified
“…Изменение образа жизни, в том числе ограничение калорийности питания, не всегда приносит желаемый, а главное, стойкий результат [4]. Попытки фармакологической коррекции избыточного веса также не принесли значимого положительного эф-фекта и, кроме того, имели достаточно много побочных эффектов [5]. Неудачи на поприще консервативных ме-тодов лечения ожирения привели к развитию относи-тельно нового направления -бариатрической хирургии, которая дает надежду на радикальное решение проблемы ожирения.…”
unclassified